The Right to Strike under Charter after Saskatchewan Federation of Labour: Applying the New Standard to Existing Regulation of Strike Activity - Etherington, Brian (Canadian Labour and Employment Law Journal, 2015)
This paper offers some predictions about the impact of the Supreme Court of Canada's landmark ruling in Saskatchewan Federation of Labour on the numerous limitations on the right to strike currently in effect in every Canadian jurisdiction. In the Saskatchewan Federation of Labour case the Court - strongly affirming its earlier decision in B.C. Health, in which it held that freedom of association under section 2(d) of the Charter encompasses the right to a "meaningful process of collective bargaining," and that "substantial interference" with that right will give rise to an infringement - declared that the right to strike is an essential component of a meaningful process of collect- ive bargaining, and as such is protected under the Charter. The author (who points out that this is not his first attempt at "reading constitutional tea leaves ") expresses surprise at the breadth of the majority's interpretation of what will constitute "substantial interference," as it is likely to result in many of the exist- ing schemes for regulation of strikes in essential services being held to violate section 2(d) and therefore to require justification under section 1 as a reason- able limit. Equally surprising, in the author's view, is the Court's section 1 analysis itself which suggests that the Court is prepared to undertake a detailed, searching review of "controlled strike" and "no-strike" schemes for designation of essential services and essential employees and the adequacy of any alterna- tive dispute resolution mechanism provided under such schemes as a substitute for the right to strike. Based on the Court's reasons in Saskatchewan Federation of Labour, the author posits that numerous Charter challenges can be expected in the coming years against legislated restrictions on collective bargaining and strike activity, including the ad hoc "instant" back-to-work model to which the federal government has repeatedly resorted. Nevertheless, he cautions, given the considerable uneveness of the jurisprudential road which led from B.C. Health to Saskatchewan Federation of Labour, one should be wary of trying to predict the course of the Supreme Court's pronouncements.